HUBUNGAN ANTARA LAMA MENJALANI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK - Iriawan, Jusron; Dwia Indah Sari,; Astri Pradini, (Journal of Innovation Research and Knowledge, 2024)
At the certain levels, the people with Chronic Kidney Disease require a therapy as the function replacement for the permanent kidney in the form of hemodialysis. Hemodialysis therapy done by the people with Chronic Kidney Disease can affect on their quality of life. This research aimed to find out the correlation between the length of hemodialysis and the quality of life of chronic kidney disease patients on hemodialysis in different hemodialysis units at Dustira Hospital. This research employed quantitative approach with cross-sectional design. The samples were selected using non probability sampling through quota sampling technique. The subjects of the current research were 112 respondents doing routine hemodialysis at Dustira Hospital. It was found that most patients with long-term hemodialysis> 6 months with poor quality of life as many as 40 people (35.7%) and with good quality as many as 16 people (14.3%). Whereas patients with long-term hemodialysis <6 months with good quality of life as many as 30 people (26.9%) and poor quality of life as many as 26 people (23.3%). Statistical test results obtained P value = 0.007 <α (0.05). There was a significant relationship between the duration of undergoing hemodialysis and the quality of life in patients with chronic kidney failure at Dustira Cimahi Hospital. This is likely to occur because patients with long hemodialysis> 6 months found that they were not too worried about the condition because they were used to the routine of undergoing hemodialysis.